Improving hand washing among school children: an educational intervention in South India - Ashutosh Shrestha; Mubashir Angolkar (Al Ameen Medical College, 2015)
Introduction: Millions of lives could be saved through simple and proper hand washing and educational interventions which are cost effective in developing world. There are marked changes in hand washing behaviour among school children after health education intervention at schools. Objective: To improve hand washing knowledge and practice among school children through health education intervention. Material and methods: Out of 7 schools Government Urdu Primary School was selected by Simple Random Sampling. All of students of grade 3rd, 4th and 5th were included. Baseline and end line survey was done in February, 2013 and September, 2013.Health education sessions were conducted once a week for six weeks. Paired t test, McNemar test and proportions were calculated. Ethical clearance and informed consent was obtained. Results: The mean knowledge score of personal hygiene was 53.86 which increased to 77.54 after health education intervention, which was statistically significant at paired t 5.17, df 6 and p<0.01. The mean practice score of personal hygiene was 41.43 which increased to 60.87 after health education intervention. The increase in correct practice was statistically significant at paired t 7.52, df 8, and p<0.001. Conclusion: The change in behavior of school children was possible if the health education intervention is properly implemented.